TINDAKAN PREVENTIF PENYEBARAN VIRUS COVID-19 DI DESA SUNGAI ALANG KECAMATAN KARANG INTAN KABUPATEN BANJAR - Herningtyas Nautika Lingga; Prima Happy Ratnapuri; Difa Intannia (Jurnal Pengabdian Kepada Masyarakat (MEDITEG), 2021)
During the Covid-19 pandemic, the Indonesian government issued a PSBB policy, but the PSBB policy has not been able to control the number of spread of Covid-19 cases. The aim of our community service is to increase understanding of Covid-19 preventive and health protocols if people have to do activities outside. The activity was carried out in Sungai Alang village, Karang Intan District, Banjar Regency for 3 days with the stages of coordination and submission of banners, delivery of materials and practices to a group of 40 women. With the program being carried out, 80% of the people know about Covid-19 and are able to take preventive actions and health protocols, so that the spread of Covid-19 decreases.